Learning and teaching early math [ the learning trajectories approach - Clements, Douglas H.; Sarama, Julie (Studies in mathematical thinking and learning, 2009)
Suitable for pre- and in-service teachers, this title shows how 'learning trajectories' help teachers become more effective professionals. It helps teachers understand the varying level of knowledge